Pengaruh Motivasi Dan Kompensasi Terhadap Kinerja Karyawan - Bella Audina; Nur Aisyah; Khalid Iskandar (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
Astra Motor Brebes 1 is a motorbike dealer that sells Honda motorbike products and provides Honda motorbike service in Ketangungan. This research has the main objective to determine the influence of Motivation and Compensation on Employee Performance at Astra Motor Brebes 1. The method used is quantitative research. The population of this study is the same as the sample size, namely 60 respondents who are employees of Astra Motor Brebes 1. The data collection technique for this research is by distributing questionnaires online using Google Form. Then the data collected was processed using SPSS 26. The results of the study showed that partially motivation had a positive effect on employee performance, namely the calculated t value was 5.930 > t table 2.005 and the sig value. (0.000 < 0.05). Partial compensation has no influence on employee performance, namely t count 1.976 < t table 2.005 and the sig value. (0.053 > 0.05). It is known that Motivation and Compensation simultaneously influence employee performance by 0.525 or 52.5%.